Sensitivity of coronary hemodynamics to vascular structure variations in health and disease - Arnav Garcha; Noelia Grande Gutiérrez (Scientific Reports)
Abstract Local hemodynamics play an essential role in the initiation and progression of coronary artery disease. While vascular geometry alters local hemodynamics, the relationship between vascular structure and hemodynamics is poorly understood. Previous computational fluid dynamics (CFD) studies have explored how anatomy influences plaque-promoting hemodynamics. For example, areas exposed to low wall shear stress (ALWSS) can indicate regions of plaque growth. However, small sample sizes, idealized geometries, and simplified boundary conditions have limited their scope. We generated 230 synthetic models of left coronary arteries and simulated coronary hemodynamics with physiologically realistic boundary conditions. We measured the sensitivity of hemodynamic metrics to changes in bifurcation angles, positions, diameter ratios, tortuosity, and plaque topology. Our results suggest that the diameter ratio between left coronary branches plays a substantial role in generating adverse hemodynamic phenotypes and can amplify the effect of other geometric features such as bifurcation position and angle, and vessel tortuosity. Introducing mild plaque in the models did not change correlations between structure and hemodynamics. However, certain vascular structures can induce ALWSS at the trailing edge of the plaque. Our analysis demonstrates that coronary artery vascular structure can provide key insight into the hemodynamic environments conducive to plaque formation and growth.